2023
DOI: 10.3390/molecules28124838
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Copper Nanoparticles: A Systematic Review of Their Features and Main Applications

Cristina M. Luque-Jacobo,
Andrea L. Cespedes-Loayza,
Talia S. Echegaray-Ugarte
et al.

Abstract: Nanotechnology is an innovative field of study that has made significant progress due to its potential versatility and wide range of applications, precisely because of the development of metal nanoparticles such as copper. Nanoparticles are bodies composed of a nanometric cluster of atoms (1–100 nm). Biogenic alternatives have replaced their chemical synthesis due to their environmental friendliness, dependability, sustainability, and low energy demand. This ecofriendly option has medical, pharmaceutical, food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 235 publications
1
5
0
Order By: Relevance
“…The nanoparticles were analyzed with NTA, which showed that the particle average size was near 100 nm with a standard deviation of 34.9 nm. The results were in unison with the previous results (Kamble et al, 2015;Ingle et al, 2022;Luque-Jacobo et al, 2023). Zeta potential was observed in the stability range, indicating the synthesis of stable CuONPs that forms stable colloid at room temperature (Gaikwad et al, 2013;Gade et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…The nanoparticles were analyzed with NTA, which showed that the particle average size was near 100 nm with a standard deviation of 34.9 nm. The results were in unison with the previous results (Kamble et al, 2015;Ingle et al, 2022;Luque-Jacobo et al, 2023). Zeta potential was observed in the stability range, indicating the synthesis of stable CuONPs that forms stable colloid at room temperature (Gaikwad et al, 2013;Gade et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Many reports of antibacterial, antifungal, larvicidal, anti-termite [ 61 , 62 , 63 , 64 , 65 ], and anticancer [ 66 , 67 ] activities of CuONPs derived from plants, animals, and microorganisms. Furthermore, several studies conducted in recent years have demonstrated the advantages of employing snail mucus to synthesize Ag and AuNPs, which have been shown to have broad-spectrum antibacterial activity, anticancer potential, and anti-inflammatory properties [ 21 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of precursor concentrations have been reported in the literature. For instance, copper chloride has been studied within a concentration range of 10 to 250 mM, copper nitrate from 0.1 to 100 mM, copper acetate from 3 to 500 mM, and copper sulfate from 1 to 1000 mM [86]. Subsequently, the reaction mixture is stirred to ensure thorough mixing with the metal precursor.…”
Section: Mechanism Of Cunp Biosynthesis With Plant Extractsmentioning
confidence: 99%